2010
DOI: 10.1021/cg901533c
|View full text |Cite
|
Sign up to set email alerts
|

Control of Morphology and Orientation of a Thin Film Tetrabenzoporphyrin (TBP) Organic Semiconductor by Solid-State Crystallization

Abstract: The grain morphology of tetrabenzoporphyrin (TBP) after solid-state crystallization by annealing from tetrabicycloporphyrin (CP) was found to be influenced by the annealing temperature, but the grain orientation was not significantly changed by the temperature. From the thin film XRD measurements, the b axis, which is the most favorite direction to enhance the carrier mobility, was found to grow in parallel to the substrate, but at high temperatures, the growth direction was slightly inclined from the substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…50 This material has a strong peak linear attenuation coefficient 51 of 3 × 10 5 cm −1 , so thin films absorb a significant fraction of light. Furthermore, tandem devices could lead to increased efficiency by overcoming the lack of absorbance at 500−650 nm and below the band gap.…”
Section: ■ Introductionmentioning
confidence: 99%
“…50 This material has a strong peak linear attenuation coefficient 51 of 3 × 10 5 cm −1 , so thin films absorb a significant fraction of light. Furthermore, tandem devices could lead to increased efficiency by overcoming the lack of absorbance at 500−650 nm and below the band gap.…”
Section: ■ Introductionmentioning
confidence: 99%
“…58 XRD measurements on MTBP thin-films have shown that molecules stack in the herringbone arrangement along the b axis, with the molecule face parallel to (114) and the HOMO orbital surface parallel to the molecule face. 36 Thus, in a and c the intermolecular spacing is small, but π orbital overlap is also small. In b, however, the intermolecular spacing is small, and the π orbital overlap is enhanced.…”
Section: Discussionmentioning
confidence: 97%
“…[32][33][34][35] Noguchi et al calculated the crystal growth characteristics of solid TBP, reporting that TBP crystallized along the b axis a) Electronic mail: pshea@umich.edu; http://www.eecs.umich.edu/omelab parallel to the substrate plane. 36 With the inherent advantages of precursor-route metallotetrabenzoporphyrins (MTBPs) in OFETs and OPVs, the study and comparison of the electronic structures of solid MTBPs is vital to understanding film behavior and device operation.…”
Section: Introductionmentioning
confidence: 99%
“…Because the (101) and (002) planes both contain the b ‐axis of the unit cell [010], a large fraction of crystallites in the latter two films have the b ‐axis is oriented perpendicular to the substrate. This texture is beneficial for charge transport in solar cells because it has been suggested that the b ‐axis of BP has better hole mobility than the a ‐ and c ‐axes due to π‐π stacking 23. The morphology of PEDOT:PSS/BP′ films comprises large rectangular columns of BP approximately 300 nm in width and 100 nm in height as shown in Figure 2g and 2h.…”
Section: Opv Device Data (Average Of Five Devices)mentioning
confidence: 99%